Prevailing usage versus priority: a revision of the types and nomenclature of the Pionus menstruus (Linnaeus, 1766) species group (Aves: Psittacidae) - Kirwan, Guy M.; Rice, Nathan H.; Jørgensen, Povl; Collar, Nigel J. (Zootaxa, 2026)
The taxonomy of Pionus menstruus has been relatively settled for at least the last 50 years, although a few recent authorities have split the Atlantic Forest population (P. m. reichenowi) from the other two subspecies (P. m. menstruus over much of Amazonia and P. m. rubrigularis in southern Central America to South America north and west of the Andes). Treated as a synonym of P. m. menstruus since the 1930s, the name Psittacus cobaltinus Massena, 1854, was generally thought to have been based on two specimens, both juveniles, said to be from ‘Colombia’. In our judgement one of these specimens (in the Natural History Museum, Tring) pertains to P. m. reichenowi and the other (at the Academy of Natural Sciences at Drexel University, Philadelphia) to P. m. menstruus. However, a reconsideration of the available evidence indicates that there is no rationale to believe that the Philadelphia specimen is a syntype and that Psittacus cobaltinus was probably based on a single specimen. All of the evidence, some of it previously unpublished, demonstrates that the Tring individual is that specimen. Because Psittacus cobaltinus has been used as a valid name since 1899, it cannot be considered a nomen oblitum under Art. 23.9 (specifically Art. 23.9.1.1 is not met). Given that Pionias Reichenowi Heine, 1884, has been in regular use only c.50 years, we advocate that priority be respected and Massena’s name is used, it being the senior synonym for this population. Available information indicates that the type material (three syntypes, in the Museum Heineanum, Halberstadt, and Museum für Naturkunde, Berlin) pertaining to Pionias Reichenowi was also mixed, although two of the specimens are either lost or destroyed. Nevertheless, to fix the taxonomic identity of this name unequivocally in favour of its long-standing attribution, we precautionarily designate the apparently only surviving syntype, in Halberstadt, as the lectotype of P. m. reichenowi. This designation will permit anyone who wishes to make an application to the ICZN in favour of prevailing usage for reichenowi over cobaltinus to do so from a solid base. Finally, there is evidence that Psittacus menstruus Linnaeus, 1766, was itself based on materials pertaining to more than one parrot species. As a result, a neotype is designated that accords with prevailing usage. The new arrangement for the species group is as follows: Pionus menstruus (Linnaeus, 1766), with subspecies P. m. rubrigularis Cabanis, 1881, and P. m. cobaltinus Massena, 1854 (syn. Pionias Reichenowi Heine, 1884, and P. m. cyanescens O. M. O. Pinto, 1960).